The level of customer satisfaction of motorzone marketing, Bansalan branch - Unabie, Reynalie; Lorna, Rejas (-- Davao del Sur: UM Bansalan College, 2012)
The services of the management of Motorzone Marketing, Bansalan Branch should have to improve more so that the level of satisfaction of the clients and customers will reach the excellent level. The prices and charges for the spare parts and motorcycle units must be more favorable to the customers. The employee of Motorzone Marketing, Bansalan Branch must undergo more training and seminars so that they will have an improvement in dealing on their customers and clients. The management should have a manager that only manages that branch of Bansalan, so that he could always see the daily happening of the branch.